Intimate mobile connections: a tool for intimacy - Lloyd, Clare (University of Canberra, 2010)
The telephone has long been understood to be a communication tool with personal attributes (Fischer 1992). The use of a mobile phone for intimate personal communication echoes and extends these uses of the telephone. This paper explores the ways in which mobile phone owners use their telephones to connect with those who are important to them. It examines the ways that mobile phones play integral roles for individuals in their relationship building and shows how mobile phones are deeply integrated into the private and intimate everyday lives of people. This paper details some of the results from a research project that focused on the meanings given, and used with mobile phone practices in Australia. The research was concerned with Communication as socially constructed. Discourse Analysis was chosen as a guiding methodology in order to focus on "texts" that revealed emerging patterns of meaning and use related to mobile phones. Interviews, collected cultural artefacts and a Research Journal provided the primary material, and Discourse Analysis was used to consider each source of information and to compare them.